Impact of Soil Organic Matter Content on Soil Moisture and Temperature at Different Depths in the Central Qinghai-Xizang Plateau - Qing FU; Kun YANG; Donghai ZGENG; Yingying CHEN (Gaoyuan qixiang)
Soil organic matter content is relatively high in the central and eastern Qinghai-Xizang Plateau， which may change the soil hydrothermal properties and thus affect the transport of soil water and heat.However， there is still a lack of systematic quantification on how soil organic matter content affects soil moisture and temperature profiles as well as their spatial heterogeneity on the Qinghai-Xizang Plateau.In this study， this effect is quantified using the in situ soil moisture and temperature data as well as soil organic carbon contents collected at 32 stations under similar climatic conditions in Naqu.The soil temperature and moisture dynamics in different depths （5， 10， 20 and 40 cm） with different organic matter contents and their spatial heterogeneity during the warm season were systematically analyzed.It is found that the soil organic matter content is a key factor determining the spatial distribution of soil moisture at 5 cm and 10 cm depth and temperature at 5 cm depth.The soil organic matter content also significantly affects the profile characteristics and dynamics of soil moisture from the surface to 20 cm depth.A higher organic matter content tends to produce a greater water holding capacity， resulting in higher soil moisture contents from the surface to 20 cm depth.In addition， the profile characteristics and variations of soil temperature are largely influenced by the soil organic matter content as well.The higher organic matter content leads to lower thermal inertia， smaller amplitudes of diurnal soil temperature variation， and thus longer time lag of heat transfer to the deeper layers.The findings of this study will provide an important reference for improving the soil moisture and temperature simulations of land surface models in alpine meadows.